Aktivitas Antiasma Nigella sativa L. Dan Amomum cardamomum Terhadap Otot Polos Bronkus, Epitel Bronkiolus, Jumlah Sel Mast, Eosinophil Mencit Asma - Gunawan Firmansyah; Gunawan Pamudji Widodo; Tri Wijayanti (Universitas Wahid Hasyim Semarang, 2024)
Asthma is a chronic respiratory inflammation that limits expiratory air flow. Black cumin reduces the infiltration of inflammatory cells in the respiratory tract comparable to class III antihistamines, cardamom suppresses the formation of a Th2 immune response and has the potential to be therapeutic for allergic asthma. This study aims to determine the profile of black cumin & cardamom essential oils using GC-MS, the effect of the combination of black cumin & cardamom in reducing the thickness of bronchial smooth muscle, bronchiolar epithelium, number of mast cells, and eosinophils in asthmatic mice. This research is an experimental Post-test Only Control Group Design, creating an OVA-induced asthma test animal model of 30 Balb/C mice divided into 6 normal groups (N), asthma control (N-), positive control (P+) and 3 treatment groups with dose variations (K1, K2, K3). Day 7 desensitization OVA 10μg+1 mg Al(OH)3 0.5mL NaCl intraperitoneally, day 14 re-desensitization OVA 20μg+2 mg Al(OH)3 1 mL NaCl. On the 21st, 23rd and 25th days, 1% OVA was inhaled. Days 26 to 39 (K1), (K2), (K3) were given a combination of black cumin oil & cardamom. On the 40th day, histopathology was terminated. The results of the study showed that in 3 groups of dose variations with (P+) the thickness of bronchial smooth muscle, bronchiolar epithelium, mast cells and eosinophils was significantly greater (p>0.05), meaning that there was no statistically significant difference as an anti-asthma, the combination of black cumin & cardamom was proven. reducing the thickness of bronchial smooth muscle, bronchiolar epithelium, number of mast cells and eosinophils in asthmatic mice with optimal doses of a combination of black cumin oil and cardamom oil in a ratio of 75:25 (K2) showed better antiasthmatic potential, compared to K1 (50:50) and K3 (25 :75).